Designing a pragmatic model for strategic purchasing of health services in health insurance companies: The feasible pivot of strategic purchasing in a developing country. Issue 1 (22nd February 2019) - Rezapour, Aziz; Hakimzadeh, Seyyed Mostafa; Panahi, Sirous; Teymourzadeh, Ehsan; Bahadori, Mohammadkarim; Bastani, Peivand; Tahernezhad, Ali
Abstract : Purpose: The purpose of this paper is to identify the most important factors for strategic purchasing of health services in the health sector by the Iran Health Insurance Company and to provide an applicable model for other similar organizations in developing countries. Design/methodology/approach: The present qualitative study was conducted in 2017 to identify the factors affecting the implementation of strategic purchasing of health services in the health sector by the Iran Health Insurance Company and to provide an indigenous and practical model through two phases: semi-structured interview followed by a Delphi process. Findings: According to the findings of this study, Ministry of Welfare, Labor and Social Security plays a central role in the strategic purchasing. In addition, this was also approved by the representatives of citizens in communities concerning professional associations, insurance agencies and representative of the Council of Ministers. Model development explored 9 themes and 54 sub-themes. Research limitations/implications: Based on the model, most attention has been paid to consumer role and inter-sector leadership of the company with other relevant organizations and systems including other insurance organizations and the welfare ministry. More importantly, the health insurance company should be able to communicate with providers and to choose the best providers, receiving price information through competition in the most appropriate mechanism. Guided by this model, it can strategically buy the best and the most effective services for its insured population. Social implications: It might help developing societies to promote their health systems based on targeting the health budgeting and financial constraints so that it is prioritized according to the strategic purchasing criteria and consequently, economic evaluation. Originality/value: The linchpins of the present study are as follow: first, the pragmatic model presented in the paper could help developing health systems to overcome the impediment in the implementation progress of strategic purchasing. Second, the model satisfies the need of enough knowledge to apply strategic purchasing in the health system. Third, the indigents have long been given special protection and consideration in the model that has continued to capture the attention of every policy-maker, in particular, developing countries, the portion of which is significant. Fourth, based on this model, attention has been paid to consumer role and inter-sector leadership of organization with other relevant organizations and systems. Fifth, this model could be correspondent for every insurance company in countries with similar developing conditions.